Knowledge of Non-Communicable Diseases among School Going Adolescents in Kathmandu - Uprety, Kamala; Uprety, Durga; Sharma, Pratima (Journal of Productive Discourse, 2025)
This study employed a descriptive cross-sectional design to assess knowledge of non-communicable diseases (NCDs) among adolescents aged 14–19 years (grades 9–12) at Mahindra Rastriya Secondary School in Kathmandu. The school was selected using simple random sampling, and complete enumeration was used for sample selection. A total of 209 respondents were surveyed through face-to-face interviews using a structured questionnaire. Descriptive and inferential statistics were applied in data analysis. Results showed that over 54% of respondents had adequate knowledge of NCDs, with greater awareness of diabetes and cardiovascular diseases. However, knowledge of cancer and chronic respiratory diseases was limited. Although awareness of cardiovascular diseases was relatively higher, only one-third of respondents were familiar with major risk factors. Rural adolescents demonstrated higher levels of knowledge, although no significant associations with socio-demographic factors were observed—contrary to findings in other studies. The study highlights gaps in adolescents’ knowledge of NCDs and recommends targeted health education interventions, as well as further research into socio-demographic influences, to enhance awareness and reduce the future burden of NCDs.